Trace Element Contents in Bone Affected by Osteomyelitis - Zaichick, Vladimir; Zaichick, Sofia (International Journal of Orthopedics and Rehabilitation, 2016)
To clarify the role of trace elements in the etiology and the pathogenesis of the osteomyelitis, a nondestructive neutron activation analysis with high resolution spectrometry of long-lived radionuclides were performed. The silver (Ag), cobalt (Co), chromium (Cr), iron (Fe), mercury (Hg), rubidium (Rb), antimony (Sb), selenium (Se), and zinc (Zn) mass fraction were estimated in normal bone samples from 27 patients with intact bone (12 females and 15 males, aged from 16 to 49 years), who had died from various non bone related causes, mainly unexpected from trauma, and in samples, obtained from open biopsies or after operation of 10 patients with osteomyelitis (3 females and 7 males, 9 to 21 years old). The reliability of difference in the results between intact bone and bone affected by osteomyelitis was evaluated by Student’s t-test. In the bone affected by osteomyelitis the mass fractions of Co, Cr, Fe, Se, and Zn are significantly higher than in normal bone tissues. In the inflamed bone tissue many correlations between trace elements found in the control group are no longer evident. In bone affected by osteomyelitis the trace element homeostasis is significantly disturbed.